Impact of concomitant medication use on belimumab efficacy and safety in patients with systemic lupus erythematosus. (December 2016) - Schwarting, A; Dooley, M A; Roth, D A; Edwards, L; Thompson, A; Wilson, B
Practicing physicians have requested efficacy and safety data for belimumab, when used with specific systemic lupus erythematosus (SLE) medications. This was a post hoc analysis of pooled efficacy and safety data from patients who received belimumab 10 mg/kg plus standard of care (SoC) or placebo (SoC) in two Phase III, randomized trials, BLISS-52 and BLISS-76. Patients were categorized into four groups based on baseline concomitant medication usage: steroids only; antimalarials (AM) only; steroids + AM; or steroids + AM + immunosuppressants (IS). The primary endpoint was the SLE Responder Index (SRI) at Week 52. SRI over time and individual SRI components were secondary endpoints. Time to first flare and changes in concomitant medications were exploratory endpoints. Safety was assessed using adverse event (AE) reporting. Across 834 patients, steroids + AM was the largest group ( n = 346, 41.5%) and AM only was the smallest ( n = 77, 9.2%). Disease duration was shortest in the steroids + AM group (5.7 years vs 6.4–7.1 years); SELENA-SLEDAI scores were similar across groups. At Week 52, the percentage of SRI responders was greatest in the steroids + AM group for belimumab 10 mg/kg (59%) compared with placebo (44%); treatment response and SRI component improvements were also observed across other groups. The probability of experiencing an SLE flare was reduced in the steroids-only group for patients who received belimumab 10 mg/kg compared with placebo (64.3% vs 78.1%; hazard ratio 0.64; 95% confidence interval: 0.42–0.96). There was little or no change in daily AM or IS dose in any group. For all groups, there was a general decrease in steroid dose over time; a quarter to a third of patients experienced decreased steroid doses at Week 52. The overall safety profile was similar across treatment arms and concomitant medication groups, with the exception of serious AEs in the steroids + AM group (belimumab 10 mg/kg 16%, placebo 8%). The efficacy and safety of belimumab in combination with SoC was demonstrated for various groupings of steroids, AM and IS. These findings may improve the understanding of the safety and efficacy of adding belimumab to different treatments.